Hubungan Future Career Orientation dengan Career Decision Making Self-Efficacy pada Mahasiswa Tingkat Akhir D-III Universitas Negeri Padang - Al Husna Melfi; Farah Aulia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Diploma education in general is expected to provide skills to students so that they can determine the career they will pursue in the future. This study was conducted in order to determine the relationship between future career orientation and career decision making self-efficacy in D-III final year students at Padang State University. This research uses a correlational quantitative approach with Pearson Product Moment analysis technique. The research sample amounted to 93 people obtained using probability sampling technique through proportionate stratified random sampling method. Data collection was carried out using measuring instruments Prospective Life Course Questionnaire Future and Work and Career Decision Making Self-Efficacy Scale-Short Form. The results showed that there was a significant positive relationship between future career orientation and career decision making self-efficacy with a correlation coefficient (r) of 0.656. This matter shows that the higher the future career orientation, the higher the career decision making self-efficacy in D-III final year students at Padang State University and so other wise.